Analisis Strategi Harga Produk, Kualitas Layanan, Dan Sistem Pembayaran Terhadap Kepuasan Konsumen Melalui Strategi Marketing: Studi Kasus Pada PT SDP Syariah Indonesia - Yudi Yanto; Fahruddin Salim; Derriawan (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2023)
The purpose of this study is to determine whether there is an influence of product prices, service quality, and payment systems both direct and indirect influences on marketing strategies, as well as all these variables, namely product prices, service quality, payment systems, and marketing strategies on consumer satisfaction. The sample used in this study was consumers who purchased houses at PT SDP Syariah Indonesia in the period 2017–2019, which was 56 consumers. Data collection was carried out by distributing questionnaires to 56 consumers using data analysis techniques using the Structural Equation Modeling (SEM) method which was processed with the help of Smart-PLS software. The results of this study are Service quality has a significant influence on marketing strategy, Product price has no effect on marketing strategy, Payment system has a positive influence on marketing strategy, Marketing strategy does not have a positive influence on consumer satisfaction, Payment system has no influence on consumer satisfaction, Service quality has a positive influence on consumer satisfaction, Product prices have a positive influence on customer satisfaction